Respon Masyarakat Terhadap Madrasah Takmiliyah Di Kabupaten Rejang Lebong - Bahri, Syaiful (TADBIR : Jurnal Studi Manajemen Pendidikan, 2018)
Madrasah Diniyah Takmiliyah (MDT) is a non-formal education which is the solution of the lack of hours of religious study at school. The Historically, this solution is to accommodate the numerous demands of various elements of society that have been raised through; demonstrations, rallies, suggestions, and even pressure on the government. Madrasah education Diniyah Takmiliyah (MDT) in the history of education entirely an initiative of the Muslim community. The Unit MDT Education with a strong legal umbrella among such as;the provisions in the Act No. 20 of 2003 on National Education system, Government Regulation No. 55 of 2007 on Religious Education and Religious Education, Government Regulation No. 48 of 2008 concerning education funding , as well as the Minister of Religious Affairs regulation No. 13 of 2014 concerning Islamic Religious Education. In Kabupaten Rejang Lebong MDT are 15 institutions. Where the communitys response to MDT is perceived as lacking, the management of MDT management is very simple and even tends to be traditional, the holding factor of MDT is strong enough and the factor of inhibiting the low awareness of the community and the difficulty of getting the fund, and the solution for the society to address the lack of religious learning hours at the majority school of apathetic parents religious learning outcomes at school, a small part of sending their children to the MDT, and a few more parents teaching their own children at home. This research is a field research associated with various existing literatures, the aims to contribute to the public as general, STAIN Curup, and Local Government Rejang Lebong Regency.